Lennie: a smartphone application with novel implications for the management of animal colonies. (July 2015) - Allwood, MA; Griffith, D; Allen, C; Reed, J; Mahmoud, QH; Brunt, KR; Simpson, JA
Researchers rely on animals for their clinical applicability and ease of monitoring. However, careful management is required to ensure the animal and financial costs are minimized. The incorporation of 'smartphone' technology in research has increased exponentially, with a focus on the development of innovative research-based applications. We have developed a smartphone application designed to address the needs of modern researchers in the management of their colonies. 'Lennie' introduces a new method for the management of small to medium-sized animal colonies. Lennie allows users wireless access to their colonies with the ability to create and edit from virtually anywhere. Lennie also offers the ability to manage colonies based on experiments by assigning animals based on priority. Experimental time-points are also recorded with integrated scheduling options using the calendar function. Lennie represents an alternative to current large-scale software options, as the application design is simple, and requires no training or manuals. As the technological landscape is constantly evolving, we must continue to find ways to improve upon current practices to ensure that research is completed with efficiency and efficacy. With this new method of animal management, researchers are able to spend less time record keeping and can focus their efforts on continued innovation.